“And Judith Set Forth” The Travels of a Heroine - Livneh, ʿAtar 1975- (2024)
Judith is a wealthy, pious, celibate, domestic(ated) widow both at the beginning of the story and at its conclusion. Comprising the central section, her peregrinations to Holofernes’ tent (Jdt 10:1–13:20) and the Jerusalem temple (Jdt 15:8–16:21) serve as an “interlude.” Her story (chs. 8–16) is thus structured as a rite de passage, opening and ending in two stable states that enclose a liminal core. This article traces the role her two journeys play in the narrative, comparison of the topographical details, encounters with foreigners, and gender roles, suggesting that Judith’s first voyage marks her separation from her community and position within it, the second her reintegration and restoration to her original status.
Keywords: Gender; rites de passage; Travel; Judith